Korelasi Kegiatan MBKM Terhadap Peningkatan Soft Skills Mahasiswa Menggunakan Metode Apriori - Dini Anjani; Novriyenni Novriyenni; Zira Fatmaira (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2024)
Soft skills are non-technical abilities that make a person able to interact and work effectively with others. This study aims to analyze the relationship between student activities of Internships and Certified Independent Study (MSIB) on improving student soft skills using the Apriori method in data mining analysis. this research uses RapidMiner analysis tools to analyze data collected from a total of 539 student data from all over Indonesia, the best association rule has been formed (best rule) which provides information about improving the soft skills of MSIB students. Tests were conducted by determining the minimum support value of 3% (0.03) and the minimum confidence of 30% (0.3). and resulted in 106 association rules. Based on the results of the analysis, it was found that the best rule of 2 itemsets has a support of 39% and a confidence of 67%, the best rule of 3 itemsets has a support of 13% and a confidence of 81%, the best rule of 4 itemsets has a support of 6% and a confidence of 82%, and the best rule of 5 itemsets has a support of 3% and a confidence of 100%. After analyzing data using the Apriori method and RapidMiner application on 539 MSIB student soft skills data, it was found that there was a significant relationship between MBKM activities followed by students and the improvement of their soft skills and these findings also show that the less frequent value is set, the more data can be processed, as well as the minimum support value and confidence value, where the smaller the value determined, the more association results will be issued.